Functional resilience of PSII, vertical distribution and ecosystem-level estimates of subsurface microphytobenthos in estuarine tidal flats. (1st July 2019) - Frankenbach, Silja; Azevedo, Andreina A.; Reis, Vanessa; Dias, Diana; Vaz, Leandro; Dias, João M.; Serôdio, João
Abstract: Most studies on sediment-inhabiting microphytobenthos are based on the biomass present on the surface layers of intertidal flats. However, large amounts of microalgal biomass are known to exist below the surface. This study tested the role of subsurface microalgal biomass as a potential source of photosynthetically active cells for the biofilm on the surface. The resilience of buried cells was evaluated by exposing samples from various depths to surface conditions and investigating the recovery of photosynthetic activity. Additionally, vertical migration by subsurface epipelic diatoms was followed at sub-millimeter scales to evaluate its role for transporting cells to the vicinity of the sediment surface. Finally the relative importance of subsurface microalgal biomass was assessed by estimating the proportion of subsurface:surface biomass for different types of sediments from the Ria de Aveiro. Vertical profiles of chlorophyll a, 10 cm-deep, were measured on samples from three intertidal sites, representative of the range of sediment characteristics found in this estuary. The ratio of total biomass to surface biomass ('subsurface biomass fraction') based on total biomass (0–10 cm depth interval; C sub, total ) and on viable biomass (between the surface and the maximum depth with significant photosynthetic recovery; C sub, viable ). The experiments showed that buried cells were able to recover photosynthetic activity within 1.5–3 h of light exposure, with the rate of recovery being dependent on depth and type of sediment. Furthermore, subsurface vertical migration was found to enable motile cells to reach the surface from layers deeper than 1 mm within a low tide period. Overall, the results showed that surface biomass (0–0.5 cm) only accounted for one fifth to one third of the total biomass present between the surface and 10 cm, and that the amount of subsurface viable biomass reached 2–3 times the biomass present at the surface. Applying the estimates of C sub, total and C sub, viable to the whole intertidal area of the Ria de Aveiro, spatially-weighted averages for subsurface biomass fractions were found to reach 3.8 and 2.1 respectively. Highlights: Buried microphytobenthos cells can recover photosynthetic activity within 3 h. Rates of recovery of photosynthetic activity vary with depth and sediment type. Subsurface vertical migration allows cells buried 1 mm deep to reach the surface. Subsurface biomass (0–10 cm) represents 3–5 times the amount at the surface (0–0.5 cm).